Analisis kesulitan membaca permulaan pada peserta didik kelas II sekolah dasar - Nur Azza Putri Anjani; St. Y. Slamet; Sukarno Sukarno (Universitas Sebelas Maret, 2024)
This research was to(1)describe the difficulties of beginning reading; (2)describe the factors that influence difficulties of beginning reading and solutions to overcome difficulties of beginning reading. This research used a qualitative research method. The data sources in this research are teachers and class II students. Data in this research were collected using observation, interviews and documentation techniques. The result found in this research that difficulties of beginning reading in second grade students at SD N Pahang IV consist of : (1)difficulty voice the writing as much as 64.64%, (2) difficulty read smoothly as much as 12.74%, (3) difficulty clarity of voice as much as 8.82%, (4) difficulty intonation as much as 11.76%, (5) difficulty pronunciation as much as 1.96%. Factors causing initial reading difficulties include lack of understanding of letter symbols, anxiety, difficulty understanding topics, lack of parental support, feelings of nervousness, lack of understanding of punctuation marks, and self-confidence. Solutions to overcome reading difficulties include using spelling methods, SAS, sounds, language experience, media “big book”, and holding additional classes.